Scale and Study of Student Attitudes Toward Business Education’s Role in Addressing Social Issues - Sleeper, Bradley J. (Journal of business ethics, 2006)
Corporations and investors are responding to recent major ethical scandals with increased attention to the social impacts of business operations. In turn, business colleges and their international accrediting body are increasing their efforts to make students more aware of the social context of corporate activity. Business education literature lacks data on student attitudes toward such education. This study found that post-scandal business students, particularly women, are indeed interested in it. Their interest is positively related to their past donation, volunteerism, and non-profit organization membership activities, whether limited or extensive. Some evidence supports the proposition that education can modify internal principles over time. We offer suggestions for classroom and program uses of these findings in hopes of enriching the vision of future business managers.